Obatoclax, the pan-Bcl-2 inhibitor sensitizes hepatocellular carcinoma cells to promote the anti-tumor efficacy in combination with immune checkpoint blockade - Jingye Li (Translational Oncology, 2021)
Bcl-2 family proteins play critical roles in regulating lymphocyte development and maintain homeostasis, and have also been proved to be involved in various cancer types development. However, the role of Bcl-2 in hepatocellular carcinoma (HCC) development has not been clearly studied. Here, we reported the pan-Bcl-2 inhibitor, obatoclax could directly inhibit HCC growth in vitro. We further demonstrated in murine HCC model that obatoclax also suppressed HCC development in vivo. We also proved that although obatoclax inhibited T cells expansion, it had no influence on T cells activation in vivo. Mechanism study revealed that obatoclax sensitized HCC cells to T cell-mediated killing. Combination therapy of obatoclax with anti-PD-1 antibody synergistically suppressed HCC development and prolonged the survival rate of tumor-bearing mice. The combination therapy promoted T cells activation and effector cytokines expression both in spleen and tumor. In summary, our results proved that obatoclax sensitized HCC cells to T cell -mediated killing. Combination of obatoclax with immune checkpoint blockade served as a promising therapeutic strategy for HCC treatment.